Pelatihan analisis data dikotomus dengan bantuan program quest bagi guru sekolah menengah pertama - M. Zainudin; Anita Dewi Utami; M. Ali Ghufron; Anis Umi Khoirotunnisa (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
The purpose of this Community Service (PKM) is to improve the ability of junior high school teachers in conducting data analysis using quests. Training was the method used in this community empowerment progam. There are lectures, questions and answers, and practice as parts of the training. Thirteen teachers from junior high schools in the Balen District of the Bojonegoro Regency in East Java took part in this program. The N-gain test was used to measure how much participants' skills have improved, and the percentage of test participants' answers were used to analyze the data. The results of this community service can improve the ability of trainees to perform dichotomous data analysis with the help of the quest program. The average satisfaction of the dichotomous data analysis training participants with the help of the quest program in terms of the material, committee, atmosphere, and media aspects used in the training was more than 81.26 or in the satisfied category